Impacts of Internet Use on Trade: New Evidence for Developed and Developing Countries. Issue 10 (9th August 2021) - Rodriguez-Crespo, Ernesto; Billon, Margarita; Marco, Rocio
ABSTRACT: This paper investigates the impact of Internet use on bilateral trade flows using a gravity model and panel data for the period 1996–2014. First, we test the positive influence of Internet use on exports for aggregate data. Second, we test the impact of Internet use on bilateral flows separately for high-income countries and low- and middle-income countries. We find a significant and positive relationship between the Internet and bilateral exports for both groups of countries. The results also show that the impacts vary from 0.03% to 0.13% depending on the levels of income. Unlike previous studies, our findings suggest that the effect of Internet use is greater for bilateral trade flows among high-income countries. We contribute to the literature by investigating the differentiated impacts of Internet use for high-income economies and low- and middle-income countries. Our study uses panel data and covers the period of the greatest Internet diffusion.